Plant-based nanoparticles targeting malaria management - Lokole, Pathy B.; Byamungu, Galilée G.; Mutwale, Paulin K.; Ngombe, Nadège K.; Mudogo, Celestin N.; Krause, Rui W. M.; Nkanga, Christian I. (Frontiers in Pharmacology, 2024)
Malaria is one of the most devastating diseases across the globe, particularly in low-income countries in Sub-Saharan Africa. The increasing incidence of malaria morbidity is mainly due to the shortcomings of preventative measures such as the lack of vaccines and inappropriate control over the parasite vector. Additionally, high mortality rates arise from therapeutic failures due to poor patient adherence and drug resistance development. Although the causative pathogen (Plasmodium spp.) is an intracellular parasite, the recommended antimalarial drugs show large volumes of distribution and low- to no-specificity towards the host cell. This leads to severe side effects that hamper patient compliance and promote the emergence of drug-resistant strains. Recent research efforts are promising to enable the discovery of new antimalarial agents; however, the lack of efficient means to achieve targeted delivery remains a concern, given the risk of further resistance development. New strategies based on green nanotechnologies are a promising avenue for malaria management due to their potential to eliminate malaria vectors (Anopheles sp.) and to encapsulate existing and emerging antimalarial agents and deliver them to different target sites. In this review we summarized studies on the use of plant-derived nanoparticles as cost-effective preventative measures against malaria parasites, starting from the vector stage. We also reviewed plant-based nanoengineering strategies to target malaria parasites, and further discussed the site-specific delivery of natural products using ligand-decorated nanoparticles that act through receptors on the host cells or malaria parasites. The exploration of traditionally established plant medicines, surface-engineered nanoparticles and the molecular targets of parasite/host cells may provide valuable insights for future discovery of antimalarial drugs and open new avenues for advancing science toward the goal of malaria eradication.